GENDER EQUALITY IN EDUCATION: A CHALLENGE FOR POLICY MAKERS - Esteves, Maria (PEOPLE: International Journal of Social Sciences, 2018)
This research is related to the importance of introducing a gender approach in educational curricula. The 2030 Agenda for Sustainable Development has defined in its 4th goal the need to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all. This means that educational systems should have in mind the need to introduce gender debate in different areas of educations, from teacher training to subject knowledge definition, to change traditional gender roles and stereotypes. Using a qualitative research methodology based in documental analyses it will be presented how some European countries have been developing efforts to include gender equality as a topic or as an interdisciplinary subject in school curricula. The research focus on how these efforts are happening in Portugal and how school curricula are not involved in it – and this is an important challenge to be met by policy makers. Some recommendations are issued to foster the goal of gender equality as a tool to improve quality in education and contribute to a more balanced society in terms of gender representation.